Experimental investigation on the influence of processing pressure on mechanical properties of pineapple leaf fiber reinforced tapioca biopolymer composites - Mohamed, Mohamed Abdirahman; Jaafar, Jamiluddin; Ibrahim, Muhammad Akmal Afiq; M. Yusup, Eliza; Siregar, Januar Parlaungan; Osman, Shahrul Azmir; Cionita, Tezara; Fitriyana, Deni Fajar; Oumer, Ahmed Nurye (UiTM Press, 2025)
The parameters employed in composite manufacturing are the primary factors influencing composite performance. This study assessed the effect of varying molding pressures on the mechanical characteristics of tapioca biopolymer (TBP) reinforced with pineapple leaf fiber (PALF) in the creation of entirely biodegradable materials. The present study selected four different molding pressures to identify the optimal processing pressure for achieving the highest mechanical properties. Samples of 30% PALF and 70% TBP were created using four different molding pressures (2 MPa, 4 MPa, 6 MPa, and 8 MPa). The findings demonstrate that PALF-TBP composites with 6 MPa molding pressure application yield the highest mechanical properties with 14.94 MPa of tensile strength, 17.46 MPa of flexural strength, and 15.31 KJ/m² of impact strength. Additionally, scanning electron microscopy (SEM) images of the fracture samples demonstrate a notable level of interfacial adhesion between the fibers and the matrix, as well as efficient stress transfer from the matrix to the fibers. The outcomes of the current study indicate that employing optimal molding pressure is essential for producing composites with superior mechanical properties.